Modified starch hydrogel as well as preparation method and application thereof
By crosslinking natural starch with polyhydroxy compounds under humid and heat conditions to form a modified starch hydrogel with a honeycomb network structure, the problem of poor mechanical properties of natural starch hydrogels is solved, and the use of chemical reagents is avoided, so as to achieve Excellent mechanical properties and environmentally friendly production process.
Patent Information
- Application Number
- CN202411536514.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-30
AI Technical Summary
Natural starch hydrogels have problems with poor mechanical properties, high brittleness and low tensile properties. At the same time, the use of chemical reagents in existing methods has risks of toxicity and environmental pollution.
Modified starch hydrogel with honeycomb network structure is formed by crosslinking natural starch with polyhydroxy compounds such as glycerol under humid and heat conditions. This method does not use chemical reagents and salts, improving the mechanical properties of the gel.
Achieve excellent mechanical properties of modified starch hydrogels, including denser network structure, smaller pore sizes and thicker pore walls, improving the toughness and mechanical properties of the gel while avoiding the toxicity and environment of chemical reagents pollute.
Smart Images

Figure CN119410034A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of starch gel, and particularly relates to a modified starch hydrogel and a preparation method and application thereof. Background Art
[0002] Hydrogel is a three-dimensional network structure composed of hydrophilic polymer chains through physical or chemical crosslinking. It has a variety of adjustable physical and chemical properties and has important application prospects in the fields of tissue engineering, drug delivery, biosensors, and intelligent robots. Starch, as a natural biomacromolecule, contains a large number of hydroxyl groups and can interact with water molecules through hydrogen bonds, showing excellent crosslinking ability, which also makes it one of the ideal materials for preparing hydrogels.
[0003] However, natural starch hydrogels generally have the disadvantages of poor mechanical properties, high brittleness and low stretchability. Arayaphan et al. found that a biodegradable double network hydrogel with excellent mechanical properties can be prepared by free radical polymerization of crosslinker polyacrylic acid in cassava starch and polyvinyl alcohol. He et al. prepared a strong hydrogel with multi-scale anisotropic structure by directional freezing and salting out.
[0004] Although the above method can improve the mechanical properties of starch hydrogel, due to the toxicity of chemical reagents, it is harmful to the human body and will cause environmental pollution; in addition, salt ions will diffuse outward in the water environment, causing serious damage to the gel structure. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a modified starch hydrogel and a preparation method and application thereof. The modified starch hydrogel provided by the present invention does not use chemical reagents and salts and has excellent mechanical properties.
[0006] In order to achieve the above object, the present invention provides the following scheme:
[0007] The invention provides a modified starch hydrogel, comprising natural starch, water and a polyhydroxy compound; the water, the polyhydroxy compound and the natural starch are cross-linked to form a honeycomb network structure.
[0008] Preferably, the polyol comprises one or more of glycerol, glucitol, sucrose, erythritol, xylitol, maltitol, D-mannitol and sorbitol; the mass of the polyol is 2-8% of the mass of the modified starch hydrogel; the mass of the water is 52-58% of the mass of the modified starch hydrogel.
[0009] Preferably, the natural starch includes one or more of potato starch, corn starch, wheat starch, sweet potato starch, cassava starch, indica rice flour, mung bean starch and pea starch; the natural starch includes amylose and amylopectin; the mass of the amylose is 20-25% of the mass of the starch; the mass of the natural starch is 40% of the mass of the modified starch hydrogel.
[0010] The present invention provides a method for preparing the modified starch hydrogel described in the above scheme, comprising the following steps:
[0011] The starch hydrogel and the polyhydroxy compound aqueous solution are mixed and subjected to a wet heat toughening treatment, in which part of the water in the starch hydrogel is replaced by the polyhydroxy compound to obtain a modified starch hydrogel; the temperature of the wet heat toughening treatment is 25 to 135°C.
[0012] Preferably, the wet heat toughening treatment is performed for 15 to 120 minutes.
[0013] Preferably, the mass ratio of the starch hydrogel to the polyol aqueous solution is (1-1.25):15; the mass concentration of the polyol in the polyol aqueous solution is 25-100%.
[0014] Preferably, the mass concentration of water molecules in the starch hydrogel is 60%.
[0015] Preferably, after the wet heat toughening treatment is completed, the product is further immersed in water; the immersion temperature is 0 to 5°C, the number of times is 1 to 5 times, and the time of a single immersion is 5 to 30 minutes.
[0016] Preferably, the preparation of the starch hydrogel comprises: gelatinizing starch slurry to obtain the starch hydrogel; the gelatinization power is 500 to 800 W, and the time is 3 to 4 minutes.
[0017] The present invention provides the use of the modified starch hydrogel described in the above scheme or the modified starch hydrogel prepared by the preparation method described in the above scheme in food.
[0018] The present invention provides a modified starch hydrogel, comprising natural starch, water and a polyhydroxy compound; the water, the polyhydroxy compound and the natural starch are cross-linked to form a honeycomb network structure. The modified starch hydrogel provided by the present invention has a honeycomb network structure. Compared with pure starch hydrogel, the modified starch hydrogel provided by the present invention has a denser gel network structure, a smaller pore size and a thicker pore wall thickness, and thus has excellent mechanical properties.
[0019] In addition, the modified starch hydrogel provided by the present invention does not use chemical reagents, will not cause harm to the human body and will not cause environmental pollution.
[0020] The present invention provides a method for preparing the modified starch hydrogel described in the above scheme. The present invention places pure starch hydrogel in an aqueous solution of a polyol compound, and optimizes the interaction between polymer-polymer (polymer is amylose) or polymer-solvent (solvent is an aqueous solution of a polyol compound) through the free movement of macromolecules during wet heat toughening treatment, thereby increasing the crystallization domain of the polymer or reducing the average distance between adjacent domains in the starch hydrogel, thereby enhancing the gel network structure in the starch hydrogel. The wet heat toughening process provides a freer and looser environment for the movement of macromolecules, increases the entanglement density between molecular chains, and makes the starch hydrogel network structure more compact and stable. The combination of solvent replacement and wet heat toughening significantly improves the toughness and mechanical properties of the starch hydrogel, and these excellent mechanical properties are mainly attributed to the synergistic effect of high crystallinity and molecular chain entanglement in the starch hydrogel.
[0021] Further, the modified starch hydrogel provided by the present invention does not use salt. At the same time, during the gelatinization process of the starch hydrogel (gelatinization reaction belongs to a physical change process), the double helix structure in the amylose molecular chain dissociates, and during the wet heat toughening process, the hydroxyl groups on the amylose molecular chain interact with the hydroxyl groups on the polyol (such as glycerol) molecules to form strong hydrogen bonds. Polyols are miscible with water, and excess polyols can replace a large number of water molecules in the starch gel, and the morphology and structure of the starch gel after the combination do not change significantly. Therefore, the preparation method provided by the present invention will not cause serious damage to the gel structure.
[0022] Furthermore, when the soaking temperature is sufficient to reach the temperature at which the polyhydroxy compound molecules and the starch molecular chains break, long-term soaking will displace the polyhydroxy compounds, but will cause starch swelling problems and seriously damage the gel network of the starch; the present invention controls the soaking temperature at 0-5°C, which will not cause serious damage to the gel network structure of the modified starch hydrogel.
[0023] The present invention provides an application of the modified starch hydrogel described in the above scheme in food preparation. Compared with the gel prepared from ordinary starch and water, the modified starch hydrogel provided by the present invention has the advantages of higher toughness and density, smaller pores, thicker pore walls, higher hardness and a chewier taste. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0025] Figure 1 The figure is a schematic diagram of the preparation process of the modified starch hydrogel of the present invention;
[0026] Figure 2 PSgel@Control of Comparative Example 7 and PSgel@Control of Comparative Example 6 100-90 and PSgel@Glycerol of Example 24 100-90 Storage modulus (G'), loss modulus (G") (A.) and loss factor tanδ (B) of the samples; in the figure, solid represents G' and hollow represents G";
[0027] Figure 3 Stress-strain curves of the modified starch hydrogel samples of Comparative Examples 8 to 12 treated at -30°C (A.) and the modified starch hydrogel samples of Comparative Examples 13 to 17 treated at -18°C (B.) for 15 min, 30 min, 60 min, 90 min and 120 min;
[0028] Figure 4 The stress-strain curves of the modified starch hydrogel samples of Comparative Examples 18 to 22 at 4° C. (C.) and the modified starch hydrogel samples of Examples 32 to 36 at 25° C. (D.) for 15 min, 30 min, 60 min, 90 min and 120 min;
[0029] Figure 5 The stress-strain curves of the modified starch hydrogel samples of Examples 37 to 41 treated at 50° C. (E.) and the modified starch hydrogel samples of Examples 42 to 46 treated at 100° C. (F.) for 15 min, 30 min, 60 min, 90 min and 120 min;
[0030] Figure 6 Stress-strain curves of the modified starch hydrogel samples of Examples 47 to 51 treated at 120° C. (G.) and the modified starch hydrogel samples of Examples 52 to 56 treated at 135° C. (H.) for 15 min, 30 min, 60 min, 90 min and 120 min;
[0031] Figure 7 PSgel@Control of Comparative Example 7 and PSgel@Control of Comparative Example 6 100-90 and PSgel@Glycerol of Example 24 100-90 The tensile curve (A.) and shear curve (B.) of
[0032] Figure 8The stress-strain curves of the sweet potato starch (A.) of Example 25 and the mung bean starch (B.) of Example 26 were measured based on the solvent replacement synergistic wet heat toughening treatment method;
[0033] Fig. 9 The stress-strain curves of the indica rice flour (C.) of Example 27 and the cassava starch (D.) of Example 28 were measured based on the solvent replacement synergistic wet heat toughening treatment method;
[0034] Fig.10 The stress-strain curves of the pea starch (E.) of Example 29 and the wheat starch (F.) of Example 30 were measured based on the solvent replacement synergistic wet heat toughening treatment method;
[0035] Fig.11 The stress-strain curve of corn starch (G.) of Example 31 was measured based on the solvent replacement synergistic wet heat toughening treatment method;
[0036] Fig.12 PSgel@Control of Comparative Example 7 (upper left picture), PSgel@Control of Comparative Example 6 100-90 (Top right) and PSgel@Glycerol of Example 24 100-90 (lower row) SEM images of cross sections;
[0037] Fig.13 PSgel@Control of Comparative Example 7 and PSgel@Control of Comparative Example 6 100-90 and PSgel@Glycerol of Example 24 100-90 Fourier transform infrared spectrum of the sample (A.) and short-range order diagram (B.);
[0038] Fig.14 PSgel@Control of Comparative Example 7 and PSgel@Control of Comparative Example 6 100-90 and PSgel@Glycerol of Example 24 100-90 X-ray diffraction patterns of the samples. DETAILED DESCRIPTION
[0039] The invention provides a modified starch hydrogel, comprising natural starch, water and a polyhydroxy compound; the water, the polyhydroxy compound and the natural starch are cross-linked to form a honeycomb network structure.
[0040] Unless otherwise specified, the materials and equipment used in the present invention are commercially available.
[0041] In the present invention, the polyhydroxy compound preferably includes one or more of glycerol, glucitol, sucrose, erythritol, xylitol, maltitol, D-mannitol and sorbitol; the mass of the polyhydroxy compound is preferably 2-8% of the mass of the modified starch hydrogel, and in the embodiments of the present invention, it can be 2%, 3%, 4%, 5%, 6%, 7% or 8%; the mass of the water is preferably 52-58% of the mass of the modified starch hydrogel, and in the embodiments of the present invention, it can be 52%, 53%, 54%, 55%, 56%, 57% or 58%.
[0042] In the present invention, the natural starch preferably includes one or more of potato starch, corn starch, wheat starch, sweet potato starch, cassava starch, indica rice flour, mung bean starch and pea starch; the starch preferably includes amylose and amylopectin; the mass of the amylose is preferably 20-25% of the mass of the starch; the mass of the natural starch is preferably 40% of the mass of the modified starch hydrogel.
[0043] The modified starch hydrogel provided by the present invention has a honeycomb network structure. Compared with pure starch hydrogel, the modified starch hydrogel provided by the present invention has a denser gel network structure, a smaller pore size, and a thicker pore wall thickness, and thus has excellent mechanical properties.
[0044] In addition, the modified starch hydrogel provided by the present invention does not use chemical reagents, will not cause harm to the human body and will not cause environmental pollution.
[0045] The present invention provides a method for preparing the modified starch hydrogel described in the above scheme, comprising the following steps:
[0046] The starch hydrogel and the polyhydroxy compound aqueous solution are mixed and subjected to a wet heat toughening treatment, during which part of the water in the starch hydrogel is replaced by the polyhydroxy compound to obtain a modified starch hydrogel.
[0047] In the present invention, the preparation of the starch hydrogel preferably comprises: gelatinizing a starch slurry to obtain the starch hydrogel.
[0048] In the present invention, the starch slurry is preferably obtained by mixing natural starch and water. In the present invention, the mass ratio of the natural starch to water is preferably 2:3. The present invention preferably puts the starch slurry into a silicone mold for gelatinization. In the present invention, the power of the gelatinization is preferably 500-800W, and in an embodiment of the present invention, it can be 500W, 550W, 600W, 650W, 700W, 750W or 800W; the gelatinization time is preferably 3-4min, and in an embodiment of the present invention, it can be 3min or 4min. In the present invention, the mass concentration of water molecules in the starch hydrogel is preferably 60%.
[0049] In the present invention, during the gelatinization process of the starch slurry, the double helix structure in the amylose molecular chain is dissociated.
[0050] After the gelatinization is completed, the present invention also preferably cools the gelatinized sample to room temperature and then demoulds it to obtain the starch hydrogel.
[0051] In the present invention, the mass ratio of the starch hydrogel to the polyol aqueous solution is preferably (1-1.25):15. In embodiments of the present invention, it may be 1:15, 1.1:15, 1.2:15 or 1.25:15.
[0052] In the present invention, the mass concentration of the polyhydroxy compound in the polyhydroxy compound aqueous solution is 25-100%. In the embodiments of the present invention, it can be 25%, 30%, 50%, 60%, 75%, 80% or 100%.
[0053] The present invention preferably places the mixed slurry of starch hydrogel and polyhydroxy compound aqueous solution into a sealed cooking bag for wet heat toughening treatment. In the present invention, the temperature of the wet heat toughening treatment is 25 to 135°C, and in the embodiments of the present invention, it can be 25°C, 30°C, 50°C, 60°C, 100°C, 120°C or 135°C; the time of the wet heat toughening treatment is preferably 15 to 120 minutes, and in the embodiments of the present invention, it can be 15 minutes, 20 minutes, 30 minutes, 50 minutes, 60 minutes, 80 minutes, 90 minutes, 100 minutes or 120 minutes.
[0054] After completing the wet heat toughening treatment, the present invention also preferably includes soaking the obtained product in water; the soaking temperature is preferably 0-5°C, and in the embodiment of the present invention, it can be 0°C, 1°C, 2°C, 3°C, 4°C or 5°C; the number of soakings is preferably 1-5 times, and in the embodiment of the present invention, it can be 1 time, 2 times, 3 times, 4 times or 5 times; the time of a single soaking is preferably 5-30 minutes, and in the embodiment of the present invention, it can be 5 minutes, 10 minutes, 20 minutes or 30 minutes. In the present invention, the soaking is preferably carried out using an ice-water mixture; the mass of the sample and the volume ratio of the ice-water mixture are preferably 1g:20mL.
[0055] The present invention can wash away the polyhydroxy compounds that have not participated in the reaction (that is, have not been combined with the natural starch during the wet heat toughening treatment) by soaking.
[0056] After the soaking is completed, the present invention also preferably uses filter paper to absorb the moisture on the surface of the sample after soaking to obtain the modified starch hydrogel.
[0057] The present invention places pure starch hydrogel in a polyol aqueous solution, optimizes the interaction between polymer-polymer (polymer is amylose) or polymer-solvent (solvent is polyol aqueous solution) by the free movement of macromolecules during wet heat toughening treatment, increases the crystallization domain of the polymer or reduces the average distance between adjacent domains in the starch hydrogel, thereby enhancing the gel network structure in the hydrogel. The wet heat toughening process provides a freer and looser environment for the movement of macromolecules, increases the entanglement density between molecular chains, and makes the starch hydrogel network structure more compact and stable. The combination of solvent replacement and wet heat toughening significantly improves the toughness and mechanical properties of the starch hydrogel, and these excellent mechanical properties are mainly attributed to the synergistic effect of high crystallinity and molecular chain entanglement in the starch hydrogel.
[0058] The modified starch hydrogel provided by the present invention does not use salt. At the same time, during the gelatinization process of the starch hydrogel (the gelatinization reaction belongs to the physical change process), the double helix structure in the amylose molecular chain dissociates, and during the wet heat toughening process, the hydroxyl groups on the amylose molecular chain interact with the hydroxyl groups on the polyol (such as glycerol) molecules to form strong hydrogen bonds. Polyols and water are mutually soluble, and excessive polyols can replace a large number of water molecules in the starch gel, and the morphology and structure of the starch gel after the combination do not change significantly. Therefore, the preparation method provided by the present invention will not cause serious damage to the gel structure.
[0059] When the soaking temperature is high enough to reach the temperature at which the polyhydroxy compound molecules and the starch molecular chains break, long-term soaking will displace the polyhydroxy compounds, but will cause starch swelling problems and seriously damage the gel network of the starch. The present invention controls the soaking temperature at 0-5°C, which will not cause serious damage to the gel network structure of the modified starch hydrogel.
[0060] The present invention provides the use of the modified starch hydrogel described in the above scheme or the modified starch hydrogel prepared by the preparation method described in the above scheme in food. Compared with the gel prepared from ordinary starch and water, the modified starch hydrogel provided by the present invention has the advantages of higher toughness and density, smaller pores, thicker pore walls, higher hardness and a chewier taste.
[0061] Figure 1 The preparation process of starch hydrogel, such as Figure 1 As shown, the present invention sequentially performs gelatinization, solvent replacement + wet heat toughening treatment and soaking and washing on a potato starch solution to obtain a final sample, namely the modified starch hydrogel.
[0062] In order to further illustrate the present invention, a modified starch hydrogel provided by the present invention and its preparation method and application are described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.
[0063] In the examples, potato starch was purchased from Gansu Lantian Potato Industry Development Co., Ltd., and glycerol (food grade) was purchased from Beijing Qingyuan Food Additive Co., Ltd.; the water used in the experimental process was deionized water; the high-temperature cooking bag was manufactured by Xizhilong, with a specification model of GWZZD.
[0064] Embodiments 1 to 4
[0065] Potato starch and deionized water were mixed in a mass ratio of 2:3 and stirred evenly to obtain starch slurry; 4 mL of starch slurry was poured into a rectangular silicone mold of 80 mm (length) × 20 mm (width) × 2 mm (thickness) and evenly smoothed; then, the mold was steamed in a steamer (500 w) for 4 min, cooled to room temperature and demolded to obtain pure starch hydrogel, recorded as PSgel@Control.
[0066] 12g of PSgel@Control sample was placed in a high-temperature cooking bag containing 180g of glycerol aqueous solution, where the mass concentration of glycerol in the glycerol aqueous solution was 25%, 50%, 75% and 100%, respectively, and subjected to wet heat toughening treatment at 100℃ for 90min;
[0067] 12 g of the sample after the wet heat toughening treatment was taken and soaked in 240 mL of deionized water (ice-water mixture at 0° C.) for 10 minutes, and the process was repeated three times. Excess water on the surface was absorbed with filter paper to obtain the modified starch hydrogel.
[0068] Comparative Example 1
[0069] The preparation steps are the same as those in Example 1, except that the mass concentration of glycerol in the glycerol water is 0%.
[0070] Tensile property test of modified starch hydrogel samples of Examples 1 to 4 and the sample obtained in Comparative Example 1
[0071] Take 4 g of PSgel@Glycerol sample, put it into 200 mL of 100°C boiling water and cook it to the optimal rehydration time (40 s, optimal rehydration time: the time when the sample is boiled in boiling water until there is no white core inside the starch gel), and measure the tensile properties of the sample.
[0072] The test conditions are as follows: use friction paper to wrap one end of the starch gel, and wrap the other end with friction paper at a distance of 1 cm. Clamp both ends with clamps, fix one end, and stretch the other end in the horizontal direction at a constant speed. When the starch gel breaks, stop stretching and record the stretched length.
[0073] The tensile strain of the sample was determined based on the change in tensile length. By comparing the tensile strain lengths of starch hydrogels soaked in different glycerol concentrations, it was found that the gel soaked in 100% glycerol concentration had the best tensile properties. Therefore, the subsequent experiments used 100% glycerol soaking concentration to prepare modified starch hydrogels. All test samples were tested within 15 minutes after reaching the optimal rehydration time.
[0074] Embodiments 5 to 9
[0075] Potato starch and deionized water were mixed in a mass ratio of 2:3 and stirred evenly to obtain starch slurry; 4 mL of starch slurry was poured into a rectangular silicone mold of 80 mm (length) × 20 mm (width) × 2 mm (thickness) and evenly smoothed; then, the mold was steamed in a steamer (500 w) for 4 min, cooled to room temperature and demolded to obtain pure starch hydrogel, recorded as PSgel@Control.
[0076] 12 g of PSgel@Control was placed in a high-temperature cooking bag containing 180 g of glycerol (glycerol mass concentration was 100%) and subjected to wet heat toughening treatment at 25°C, 50°C, 100°C, 120°C and 135°C for 90 min respectively;
[0077] 12 g of the sample after the wet heat toughening treatment was taken and soaked in 240 mL of deionized water (ice-water mixture at 0° C.) for 10 minutes, and the process was repeated three times. Excess water on the surface was absorbed with filter paper to obtain the modified starch hydrogel.
[0078] Comparative Examples 2 to 4
[0079] The only difference from Example 5 is that the wet heat toughening treatment is changed to freeze aging treatment or low temperature aging treatment, that is, the wet heat toughening treatment is carried out at -30°C and -18°C respectively (Comparative Examples 2 and 3), and the low temperature aging treatment is carried out at 4°C (Comparative Example 4).
[0080] Tensile property test of modified starch hydrogels obtained in Examples 5 to 9 and samples obtained in Comparative Examples 2 to 4
[0081] According to the test method of Example 1, it is believed that the wet heat toughening treatment temperature is 100° C., so the subsequent experiments selected the temperature of 100° C. to prepare the required modified starch hydrogel. All test samples were tested within 15 minutes after reaching the optimal rehydration time.
[0082] Embodiments 10 to 14
[0083] Potato starch and deionized water were mixed in a mass ratio of 2:3 and stirred evenly to obtain starch slurry; 4 mL of starch slurry was poured into a rectangular silicone mold of 80 mm (length) × 20 mm (width) × 2 mm (thickness) and evenly smoothed; then, the mold was steamed in a steamer (500 w) for 4 min, cooled to room temperature and demolded to obtain pure starch hydrogel, recorded as PSgel@Control.
[0084] 12 g of PSgel@Control was placed in a high-temperature cooking bag containing 180 g of glycerol (glycerol mass concentration was 100%) and subjected to wet heat toughening treatment at 100°C for 15 min, 30 min, 60 min, 90 min and 120 min respectively;
[0085] 12 g of the sample after the wet heat toughening treatment was taken and soaked in 240 mL of deionized water (ice-water mixture at 0° C.) for 10 minutes, and the process was repeated three times. Excess water on the surface was absorbed with filter paper to obtain the modified starch hydrogel.
[0086] Tensile property test of modified starch hydrogel obtained in Examples 10 to 14
[0087] According to the test method of Example 1, it is believed that the best effect is achieved when the wet heat toughening treatment time is 90 minutes, so the subsequent experiments use a time of 90 minutes to prepare the required modified starch hydrogel. All test samples were tested within 15 minutes after reaching the optimal rehydration time.
[0088] Embodiments 15 to 18
[0089] Potato starch and deionized water were mixed in a mass ratio of 2:3 and stirred evenly to obtain starch slurry; 4 mL of starch slurry was poured into a rectangular silicone mold of 80 mm (length) × 20 mm (width) × 2 mm (thickness) and evenly smoothed; then, the mold was steamed in a steamer (500 w) for 4 min, cooled to room temperature and demolded to obtain pure starch hydrogel, recorded as PSgel@Control.
[0090] 12 g of PSgel@Control was placed in a high-temperature cooking bag containing 180 g of glycerol (glycerol mass concentration was 100%) and subjected to wet heat toughening treatment at 100°C for 90 min;
[0091] 12 g of the treated sample was taken and soaked in 240 mL of deionized water (ice-water mixture at 0° C.) for 5 min, 10 min, 20 min, and 30 min, respectively, and repeated three times. Excess surface water was absorbed with filter paper to obtain the modified starch hydrogel.
[0092] Comparative Example 5
[0093] The only difference from Example 15 is that the soaking and washing time is 0 min, that is, no soaking is performed.
[0094] Tensile property test of the modified starch hydrogels obtained in Examples 15 to 18 and the samples obtained in Comparative Example 5
[0095] According to the test method of Example 1, it is believed that the best effect is achieved when the water is soaked for 10 minutes, so the subsequent experiments use a time of 10 minutes to prepare the required modified starch hydrogel. All test samples were tested within 15 minutes after reaching the optimal rehydration time.
[0096] Examples 19 to 23
[0097] Potato starch and deionized water were mixed in a mass ratio of 2:3 and stirred evenly to obtain starch slurry; 4 mL of starch slurry was poured into a rectangular silicone mold of 80 mm (length) × 20 mm (width) × 2 mm (thickness) and evenly smoothed; then, the mold was steamed in a steamer (500 w) for 4 min, cooled to room temperature and demolded to obtain pure starch hydrogel, recorded as PSgel@Control.
[0098] 12 g of PSgel@Control was placed in a high-temperature cooking bag containing 180 g of glycerol (glycerol mass concentration was 100%) and subjected to wet heat toughening treatment at 100°C for 90 min;
[0099] Take 12 g of the sample after the wet heat toughening treatment, soak and wash it in 240 mL of deionized water (ice-water mixture at 0°C) for 10 minutes, repeat 1, 2, 3, 4 and 5 times, and use filter paper to absorb excess water on the surface to obtain the modified starch hydrogel.
[0100] Tensile property test of modified starch hydrogel obtained in Examples 19 to 23
[0101] According to the test method of Example 1, it is believed that the best effect is achieved when the sample is soaked and washed with water for 3 times, so the subsequent experiments select soaking and washing with water for 3 times to prepare the required modified starch hydrogel. All test samples were tested within 15 minutes after reaching the optimal rehydration time.
[0102] Embodiment 24
[0103] Potato starch and deionized water were mixed in a mass ratio of 2:3 and stirred evenly to obtain starch slurry; 4 mL of starch slurry was poured into a rectangular silicone mold of 80 mm (length) × 20 mm (width) × 2 mm (thickness) and evenly smoothed; then, the mold was steamed in a steamer (500 w) for 4 min, cooled to room temperature and demolded to obtain pure starch hydrogel, recorded as PSgel@Control.
[0104] 12 g of PSgel@Control sample was placed in a high-temperature cooking bag containing 180 g (100% glycerol mass concentration) and subjected to wet heat toughening treatment at 100 °C for 90 min;
[0105] Take 12 g of the sample after the wet heat toughening treatment, soak it in 240 mL of deionized water (ice-water mixture at 0°C) for 10 minutes, repeat three times, and use filter paper to absorb excess water on the surface to obtain the modified starch hydrogel, in which water content is 54 wt.%, glycerol is 6 wt.%, and starch is 40 wt.%.
[0106] Comparative Example 6
[0107] The only difference from Example 24 is that the PSgel@Control sample is placed in a high-temperature cooking bag (the high-temperature cooking bag does not contain any water or glycerin) and subjected to wet heat toughening treatment at 100°C for 90 minutes to obtain a sample (without soaking and washing), which is recorded as PSgel@Control 100-90 .
[0108] Comparative Example 7
[0109] Potato starch and deionized water were mixed in a mass ratio of 2:3 and stirred to obtain starch slurry; 4 mL of starch slurry was poured into a rectangular silicone mold of 80 mm (length) × 20 mm (width) × 2 mm (thickness) and evenly smoothed; then, the mold was steamed in a steamer (500 w) for 4 min, cooled to room temperature and demolded to obtain pure starch hydrogel, recorded as PSgel@Control, in which water accounted for 60 wt.%.
[0110] Embodiments 25 to 31
[0111] Sweet potato starch, mung bean starch, indica rice flour, cassava starch, pea starch, wheat starch, corn starch and deionized water were mixed in a mass ratio of 2:3 and stirred evenly to obtain starch slurry; 4 mL of starch slurry was poured into a rectangular silicone mold of 80 mm (length) × 20 mm (width) × 2 mm (thickness) and evenly smoothed; then, the mold was steamed in a steamer (500 w) for 4 min, cooled to room temperature and then demolded to obtain pure starch hydrogel, recorded as PSgel@Control.
[0112] 12 g of PSgel@Control was placed in a high-temperature cooking bag containing 180 g of glycerol (glycerol mass concentration was 100%) and subjected to wet heat toughening treatment at 100°C for 90 min;
[0113] 12 g of the sample after the wet heat toughening treatment was taken and soaked in 240 mL of deionized water (ice-water mixture at 0° C.) for 10 minutes, and the process was repeated three times. Excess water on the surface was absorbed with filter paper to obtain the modified starch hydrogel.
[0114] Comparative Examples 8 to 12
[0115] Potato starch and deionized water were mixed in a mass ratio of 2:3 and stirred evenly to obtain starch slurry; 4 mL of starch slurry was poured into a rectangular silicone mold of 80 mm (length) × 20 mm (width) × 2 mm (thickness) and evenly smoothed; then, the mold was steamed in a steamer (500 w) for 4 min, cooled to room temperature and demolded to obtain pure starch hydrogel, recorded as PSgel@Control.
[0116] 12 g of PSgel@Control was placed in a high-temperature cooking bag containing 180 g of glycerol (glycerol mass concentration was 100%) and subjected to freeze aging treatment at -30°C for 15 min, 30 min, 60 min, 90 min and 120 min respectively;
[0117] After the freeze-aging treatment, 12 g of the sample was taken and soaked in 240 mL of deionized water (0° C. ice-water mixture) for 10 min, and the mixture was repeated three times. The excess water on the surface was removed with filter paper to obtain the modified starch hydrogel, which was recorded as PSgel@Glycerol -30-15 、PSgel@Glycerol -30-30 、PSgel@Glycerol -30-60 、PSgel@Glycerol -30-90 and PSgel@Glycerol -30-120 .
[0118] Comparative Examples 13 to 17
[0119] Potato starch and deionized water were mixed in a mass ratio of 2:3 and stirred evenly to obtain starch slurry; 4 mL of starch slurry was poured into a rectangular silicone mold of 80 mm (length) × 20 mm (width) × 2 mm (thickness) and evenly smoothed; then, the mold was steamed in a steamer (500 w) for 4 min, cooled to room temperature and demolded to obtain pure starch hydrogel, recorded as PSgel@Control.
[0120] 12 g of PSgel@Control was placed in a high-temperature cooking bag containing 180 g of glycerol (glycerol mass concentration was 100%) and subjected to freeze aging treatment at -18°C for 15 min, 30 min, 60 min, 90 min and 120 min respectively;
[0121] After the freeze-aging treatment, 12 g of the sample was taken and soaked in 240 mL of deionized water (0° C. ice-water mixture) for 10 min, and the mixture was repeated three times. The excess water on the surface was removed with filter paper to obtain the modified starch hydrogel, which was recorded as PSgel@Glycerol -18-15 、PSgel@Glycerol -18-30 、PSgel@Glycerol -18-60 、PSgel@Glycerol -18-90 and PSgel@Glycerol -18-120 .
[0122] Comparative Examples 18 to 22
[0123] Potato starch and deionized water were mixed in a mass ratio of 2:3 and stirred evenly to obtain starch slurry; 4 mL of starch slurry was poured into a rectangular silicone mold of 80 mm (length) × 20 mm (width) × 2 mm (thickness) and evenly smoothed; then, the mold was steamed in a steamer (500 w) for 4 min, cooled to room temperature and demolded to obtain pure starch hydrogel, recorded as PSgel@Control.
[0124] 12 g of PSgel@Control was placed in a high-temperature cooking bag containing 180 g of glycerol (glycerol mass concentration was 100%) and subjected to low-temperature aging treatment at 4°C for 15 min, 30 min, 60 min, 90 min and 120 min respectively;
[0125] After the treatment, 12 g of the sample was taken and soaked in 240 mL of deionized water (ice-water mixture at 0° C.) for 10 min, and the mixture was repeated three times. The excess water on the surface was removed with filter paper to obtain the modified starch hydrogel, which was recorded as PSgel@Glycerol 4-15 、PSgel@Glycerol 4-30 、PSgel@Glycerol 4-60 、PSgel@Glycerol 4-90 and PSgel@Glycerol 4-120 .
[0126] Embodiments 32 to 36
[0127] Potato starch and deionized water were mixed in a mass ratio of 2:3 and stirred evenly to obtain starch slurry; 4 mL of starch slurry was poured into a rectangular silicone mold of 80 mm (length) × 20 mm (width) × 2 mm (thickness) and evenly smoothed; then, the mold was steamed in a steamer (500 w) for 4 min, cooled to room temperature and demolded to obtain pure starch hydrogel, recorded as PSgel@Control.
[0128] 12 g of PSgel@Control was placed in a high-temperature cooking bag containing 180 g of glycerol (glycerol mass concentration was 100%) and subjected to wet heat toughening treatment at 25°C for 15 min, 30 min, 60 min, 90 min and 120 min respectively;
[0129] After the wet heat toughening treatment, 12 g of the sample was taken and soaked in 240 mL of deionized water (0° C. ice water mixture) for 10 min, and the mixture was repeated three times. The excess water on the surface was removed with filter paper to obtain the modified starch hydrogel, which was recorded as PSgel@Glycerol 25-15 、PSgel@Glycerol 25-30 、PSgel@Glycerol 25-60 、PSgel@Glycerol 25-90 and PSgel@Glycerol 25-120 .
[0130] Embodiments 37 to 41
[0131] Potato starch and deionized water were mixed in a mass ratio of 2:3 and stirred evenly to obtain starch slurry; 4 mL of starch slurry was poured into a rectangular silicone mold of 80 mm (length) × 20 mm (width) × 2 mm (thickness) and evenly smoothed; then, the mold was steamed in a steamer (500 w) for 4 min, cooled to room temperature and demolded to obtain pure starch hydrogel, recorded as PSgel@Control.
[0132] 12 g of PSgel@Control was placed in a high-temperature cooking bag containing 180 g of glycerol (glycerol mass concentration was 100%) and subjected to wet heat toughening treatment at 50°C for 15 min, 30 min, 60 min, 90 min and 120 min respectively;
[0133] After the wet heat toughening treatment, 12 g of the sample was taken and soaked in 240 mL of deionized water (0° C. ice water mixture) for 10 min, and repeated three times. The excess water on the surface was absorbed with filter paper to obtain the modified starch hydrogel, which was recorded as PSgel@Glycerol 50-15 、PSgel@Glycerol 50-30 、PSgel@Glycerol 50-60 、PSgel@Glycerol 50-90 and PSgel@Glycerol 50-120 .
[0134] Embodiments 42 to 46
[0135] Potato starch and deionized water were mixed in a mass ratio of 2:3 and stirred evenly to obtain starch slurry; 4 mL of starch slurry was poured into a rectangular silicone mold of 80 mm (length) × 20 mm (width) × 2 mm (thickness) and evenly smoothed; then, the mold was steamed in a steamer (500 w) for 4 min, cooled to room temperature and demolded to obtain pure starch hydrogel, recorded as PSgel@Control.
[0136] 12 g of PSgel@Control was placed in a high-temperature cooking bag containing 180 g of glycerol (glycerol mass concentration was 100%) and subjected to wet heat toughening treatment at 100°C for 15 min, 30 min, 60 min, 90 min and 120 min respectively;
[0137] After the wet heat toughening treatment, 12 g of the sample was taken and soaked in 240 mL of deionized water (0° C. ice water mixture) for 10 min, and the mixture was repeated three times. The excess water on the surface was removed with filter paper to obtain the modified starch hydrogel, which was recorded as PSgel@Glycerol 100-15 、PSgel@Glycerol 100-30 、PSgel@Glycerol 100-60 、PSgel@Glycerol 100-90 and PSgel@Glycerol 100-120 .
[0138] Embodiments 47 to 51
[0139] Potato starch and deionized water were mixed in a mass ratio of 2:3 and stirred evenly to obtain starch slurry; 4 mL of starch slurry was poured into a rectangular silicone mold of 80 mm (length) × 20 mm (width) × 2 mm (thickness) and evenly smoothed; then, the mold was steamed in a steamer (500 w) for 4 min, cooled to room temperature and demolded to obtain pure starch hydrogel, recorded as PSgel@Control.
[0140] 12 g of PSgel@Control was placed in a high-temperature cooking bag containing 180 g of glycerol (glycerol mass concentration was 100%) and subjected to wet heat toughening treatment at 120°C for 15 min, 30 min, 60 min, 90 min and 120 min respectively;
[0141] After the wet heat toughening treatment, 12 g of the sample was taken and soaked in 240 mL of deionized water (0° C. ice-water mixture) for 10 min, and the mixture was repeated three times. The excess water on the surface was removed with filter paper to obtain the modified starch hydrogel, which was recorded as PSgel@Glycerol 120-15 、PSgel@Glycerol 120-30、PSgel@Glycerol 120-60 、PSgel@Glycerol 120-90 and PSgel@Glycerol 120-120 .
[0142] Embodiments 52 to 56
[0143] Potato starch and deionized water were mixed in a mass ratio of 2:3 and stirred evenly to obtain starch slurry; 4 mL of starch slurry was poured into a rectangular silicone mold of 80 mm (length) × 20 mm (width) × 2 mm (thickness) and evenly smoothed; then, the mold was steamed in a steamer (500 w) for 4 min, cooled to room temperature and demolded to obtain pure starch hydrogel, recorded as PSgel@Control.
[0144] 12 g of PSgel@Control was placed in a high-temperature cooking bag containing 180 g of glycerol (glycerol mass concentration was 100%) and subjected to wet heat toughening treatment at 135°C for 15 min, 30 min, 60 min, 90 min and 120 min respectively;
[0145] After the wet heat toughening treatment, 12 g of the sample was taken and soaked in 240 mL of deionized water (0° C. ice water mixture) for 10 min, and the mixture was repeated three times. The excess water on the surface was removed with filter paper to obtain the modified starch hydrogel, which was recorded as PSgel@Glycerol 135-15 、PSgel@Glycerol 135-30 、PSgel@Glycerol 135-60 、PSgel@Glycerol 135-90 and PSgel@Glycerol 135-120 .
[0146] Determination of rheological properties of high-toughness starch hydrogel
[0147] The rheological properties of starch hydrogels were measured using an interfacial rheometer (Anton Paar MCR102) using the previously reported method (Feng et al., 2023) with slight modifications. The test conditions were as follows: the test plate diameter was 50 mm; the test rotor model was PP50; the gap between the rotor and the plate was set to 2 mm; the test strain was 1%; the angular frequency range was 0.1-100 rad / s, and the storage modulus (G') and loss modulus (G") of the hydrogel were tested as a function of the angular frequency (w). Figure 2 As shown, PSgel@Control of Comparative Example 7 and PSgel@Control of Comparative Example 6 100-90 and PSgel@Glycerol of Example 24100-90 Storage modulus (G'), loss modulus (G") (A.) and loss factor tanδ (B) of the samples; in the figure, solid represents G' and hollow represents G''.
[0148] G' and G" are used to evaluate the rheological behavior of the hydrogel network. G' is the energy elastically stored in the specimen during cyclic stress application, G" represents the energy lost in the specimen, and tanδ reflects the relative contribution of the elastic and viscous components to the viscoelastic properties of the specimen.
[0149] Figure 2 Figure A shows the functional relationship curve of G' and G" of starch hydrogel with frequency. From the curve, we can see that in the entire frequency scanning range, the G' of all samples is significantly higher than the corresponding G", which indicates that all samples in this frequency range are elastic gels rather than viscous sols, showing a strong gel network structure or solid-like behavior. As the frequency increases from 1 rad / s to 100 rad / s, the G' and G" of all samples gradually increase without obvious crossover, indicating that the gel properties dominate in this frequency range. In the frequency scanning range of 1 to 100 rad / s, the viscoelastic modulus of all samples increases with the increase of frequency, indicating that the viscoelastic modulus is frequency-dependent. This phenomenon is attributed to the strong hydrogen bond interaction between the hydroxyl (OH) in the glycerol molecule and the hydroxyl (C-OH) on the starch molecular chain when the glycerol and water in the starch hydrogel undergo solvent replacement. In addition, during the wet heat toughening process, high temperature can promote the free movement of macromolecules, causing the weak crosslinking points between the molecular chains to dissociate. The dissociated molecular chains form new strong hydrogen bonds or tighter helical structures in the presence of glycerol macromolecules, and the conformation of the molecular chains changes to form a highly entangled gel network. As a result, the network structure in the starch gel becomes more compact and stable, thereby increasing the modulus of the gel. Solvent replacement and wet heat toughening treatment significantly enhance the solid behavior of starch-based hydrogels. Compared with PSgel@Control, PSgel@Glycerol 100-90 The G' value of the samples increased by 138.9% at 10 rad / s, which further indicated that the gel network of the starch hydrogel was significantly enhanced.
[0150] Tanδ is the ratio of G′ to G″, which can be used to reflect the damping characteristics of the sample. Figure 2 As shown in Figure B, the tanδ of all samples is between 0.1 and 0.25, which indicates that G' plays a dominant role in determining the rheological behavior of the gel (Gao et al., 2023). According to relevant research reports, when tanδ < 0.1, the gel is relatively solid, and when 0.1 < tanδ < 1, the gel is in a weak gel state (Mauro et al., 2023). Figure 2 As can be seen in Figure B, with the increase of frequency, PSgel@Glycerol 100-90 The tanδ value of the sample gradually increases, indicating that the sample gradually tends to be a weak gel. This may be attributed to the fact that the gel absorbs water and swells during the second solvent replacement process, resulting in damage to the network structure and affecting its mechanical properties.
[0151] Determination of tensile and shear properties of high-toughness starch hydrogels
[0152] According to the previously reported method (Gao et al., 2023), with slight modifications, the tensile and shear properties of all gel samples after rehydration were measured using a texture analyzer (TA.XTPlus, Stable Micro Systems, Surrey, UK). The tensile performance test parameters are as follows: the trigger force is 5g, and the stop acquisition point is the "target position". The speeds before, during and after the measurement are set to 3, 1, and 3mm8, respectively, and the strain height is 10mm. The sample parameters are set to a width of 2mm, a length of 18mm, and a stress area of 36m 2 . The shear performance test parameters were set as follows: the speeds before, during and after the test were set to 2 mm / s, 0.17 mm / s and 10 mm / s respectively, the deformation degree was 80%, and the strain height was 10 mm. The tensile and shear data were the average values of 10 measurements. According to the TPA procedure, the stress-strain curve, toughness, texture hardness and chewing hardness of the samples can be obtained. All samples were completed within 15 minutes after reaching the optimal cooking time.
[0153] Figures 3 to 6 The stress-strain curves of pure starch hydrogel samples treated with wet heat toughening at different temperatures and for different times are shown. Figure 3 Stress-strain curves of the modified starch hydrogel samples of Comparative Examples 8 to 12 treated at -30°C (A.) and the modified starch hydrogel samples of Comparative Examples 13 to 17 treated at -18°C (B.) for 15 min, 30 min, 60 min, 90 min and 120 min; Figure 4 The stress-strain curves of the modified starch hydrogel samples of Comparative Examples 18 to 22 at 4° C. (C.) and the modified starch hydrogel samples of Examples 32 to 36 at 25° C. (D.) for 15 min, 30 min, 60 min, 90 min and 120 min; Figure 5 The stress-strain curves of the modified starch hydrogel samples of Examples 37 to 41 treated at 50° C. (E.) and the modified starch hydrogel samples of Examples 42 to 46 treated at 100° C. (F.) for 15 min, 30 min, 60 min, 90 min and 120 min; Figure 6Stress-strain curves of the modified starch hydrogel samples of Examples 47 to 51 treated at 120°C (G.) and the modified starch hydrogel samples of Examples 52 to 56 treated at 135°C (H.) for 15 min, 30 min, 60 min, 90 min and 120 min. Figures 3 to 6 It can be seen from A to H that with the increase of temperature and time, the stress and strain of the hydrogel gradually increase. However, when the temperature exceeds 100℃ and the time exceeds 90min, the stress and strain of the sample gradually decrease. This phenomenon can be attributed to the following points: First, too high temperature will destroy the cross-linking bonds in the molecular chain, and a large number of cracks and damage will appear in the cross-linking structure inside the gel, resulting in uneven force during stretching. Secondly, when the temperature is too high, the macromolecular chain segments will break due to excessively violent movement, and the breakage of the chain segments will destroy the three-dimensional network structure of the gel, thereby weakening the tensile properties of the gel network. Third, at high temperatures, the glycerol macromolecules will redistribute inside the gel and agglomerate at the cross-linking points of the molecular chains to form high-hardness crystal domains. As the temperature gradually increases, the glycerol molecules will collide with the starch molecules too frequently, resulting in a weakening of the interaction force between the two, which in turn damages the network structure of the gel and deteriorates the tensile properties. Based on the above research results, we found that when the wet heat toughening treatment conditions are 100℃ and 90min, the gel has the optimal stress and strain. Therefore, this condition was selected for the subsequent experimental samples.
[0154] Figure 7 PSgel@Control of Comparative Example 7 and PSgel@Control of Comparative Example 6 100-90 and PSgel@Glycerol of Example 24 100-90 The tensile (A.) and shear curves (B.) of natural starch hydrogels are usually characterized by high brittleness (i.e., low toughness) and poor tensile properties. In the present invention, the hydrogel prepared based on the solvent replacement synergistic wet heat toughening strategy has good tensile and shear properties. Figure 7 As can be seen in A, compared with the control group, PSgel@Glycerol 100-90 The tensile strain of the samples increased from 334.35% (PSgel@Control) to 221.87% (PSgel@Control 100-90 ) increased to 479.72% (PSgel@Glycerol 100-90 ), the tensile stress increased from 383Pa (PSgel@Control) to 572.83Pa (PSgel@Control 100-90 ) increased to 795Pa (PSgel@Glycerol 100-90 ).from Figure 7 As can be seen in B, PSgel@Glycerol100-90 The shear stress of the samples increased from 760.70Pa (PSgel@Control) to 1452.70Pa (PSgel@Control 100-90 ) increased to 2407Pa (PSgel@Glycerol 100-90 ). Table 1 shows the PSgel@Control of Comparative Example 7 and the PSgel@Control of Comparative Example 6. 100-90 and PSgel@Glycerol of Example 24 100-90 Shear property data.
[0155] Table 1PSgel@Control, PSgel@Control 100-90 and PSgel@Glycerol 100-90 Shear properties
[0156] sample Toughness(g / sec) Texture hardness(g) Chewing hardness (g) Chewing property(g / sec) PSgel@Control <![CDATA[6.4443±0.11 c ]]> <![CDATA[42.9747±1.85 c ]]> <![CDATA[316.7053±12.18 c ]]> <![CDATA[713.3717±12.62 c ]]> <![CDATA[PSgel@Control 100-90 ]]> <![CDATA[12.2420±0.47 b ]]> <![CDATA[59.5900±2.96 b ]]> <![CDATA[658.4627±23.49 b ]]> <![CDATA[1116.2707±75.32 b ]]> <![CDATA[PSgel@Glycerol 100-90 ]]> <![CDATA[20.9603±1.72 a ]]> <![CDATA[90.7090±5.25 a ]]> <![CDATA[881.6790±70.43 a ]]> <![CDATA[1740.5823±60.28 a ]]>
[0157] Data are presented as mean ± standard deviation (n = 3). Mean values marked with different letters (a-c) in the same column are statistically significant (p < 0.05).
[0158] As shown in Table 1, compared with the control group, PSgel@Glycerol 100-90 The toughness of the samples increased from 6.4443 g / sec (PSgel@Control) to 12.2420 g / sec (PSgel@Control 100-90 ) significantly increased to 20.9603 g / sec (PSgel@Glycerol 100-90 ); chewing hardness increased from 316.7053g and 658.4627g to 881.6790g, and texture hardness increased from 42.9747g and 59.5900g to 90.7090g; PSgel@Glycerol 100-90The excellent mechanical properties of the sample may be attributed to the entanglement of polymer chains and the increase of crystalline domains. Previous studies have found that wet heat toughening treatment can induce high entanglement of macromolecular chains in the amorphous region and improve the crystallinity in the crystalline region. In the amorphous phase, when the highly entangled molecular chains are stretched, the entanglement points on the molecular chains will transfer tension to other chains along the direction of the molecular chains like sliding chains. The entire gel network contains many entanglement points, which can increase the tensile tension on the molecular chains. Therefore, a large amount of energy is required to untangle these entanglement points during the stretching process, thereby generating a large tensile stress. At the same time, a higher stretching rate is required to straighten the curled macromolecular chains, which will generate a higher tensile strain. In the crystalline phase (starch is divided into crystalline and amorphous regions, and the crystalline phase can also be called the crystalline region), from a physical analysis, the dense crystalline domains can serve as closely arranged cross-linking points to enhance the strength of the hydrogel. The higher the crystallinity, the stronger the gel strength, the greater the energy required to break the double helix structure, and the greater the force required to destroy the orderly arranged macromolecular chains, which can further explain the reason for the increase in tensile stress and strain. In addition, due to the synergistic effect of the high degree of entanglement in the molecular chain and the expansion of the crystallization domain, when the shear pressure encounters the crystallized molecular chain, due to the pinning effect (the pinning effect refers to the fact that when the sample is subjected to external force, its position or state remains relatively stable and does not change significantly. As the internal crystallization domain increases, when the shear pressure reaches a certain strain degree, the stress of its action will increase), the shear stress required to achieve a specific shear deformation will increase accordingly. Therefore, PSgel@Glycerol 100-90 The toughness, chewing hardness and texture hardness of the samples were also significantly enhanced.
[0159] In short, the synergistic effect of the high entanglement of molecular chains and dense crystalline domains in the hydrogel is the key to PSgel@Glycerol 100-90 The reason for its high strength, toughness and elongation.
[0160] Determination of texture properties of high toughness starch hydrogel
[0161] According to the previously reported method (Jia et al., 2022), some modifications were made and a texture analyzer (TA.XTPlus, Stable Micro Systems, Surrey, UK) was used to measure the texture properties of all gel samples after rehydration. The test conditions were as follows: the TPA program was selected, equipped with a P / 36R probe, and a compression-decompression cycle mode was used. The analysis was stopped at the "target position", the pre- and post-measurement speeds were set to 5 mm / s, the speed during the measurement was set to 1 mm / s, the contact force was 5 g, the deformation degree was set to 30%, the strain height was set to 10 mm, the length of the sample was set to 20 mm, the width was 20 mm, and the thickness was 2 mm. According to the TPA procedure, parameters such as gel hardness, elasticity, adhesion, cohesion and resilience were determined. The texture data is the average of 10 measurement data, and all samples were completed within 15 minutes after reaching the optimal cooking time. Table 2 shows the PSgel@Control of Comparative Example 7 and the PSgel@Control of Comparative Example 6. 100-90 and PSgel@Glycerol of Example 24 100-90 The texture characteristics of the samples include indicators such as gel hardness, viscosity, elasticity and chewiness.
[0162] Table 2PSgel@Control, PSgel@Control 100-90 and PSgel@Glycerol 100-90 Texture characteristics
[0163]
[0164] As shown in Table 2, compared with the control group, PSgel@Glycerol 100-90 The gel hardness of the samples increased from 1653.6763g (PSgel@Control) to 1578.1617g (PSgel@Control). 100-90 ) increased to 2092.449g (PSgel@Glycerol 100-90 ), which may be attributed to the fact that the wet heat toughening treatment will intensify the free movement of macromolecules, rearrange the starch molecular chains, and dissociate and reorganize the weak crosslinking points between the chains to form new strong crosslinking points. In addition, the strong hydrogen bond interaction formed by the hydroxyl group between the glycerol macromolecules and the starch macromolecules will further enhance the strength of the gel network, thereby forming a more dense and stable gel network structure and improving the hardness of the gel. The adhesion increased from -279.1840 g·s (PSgel@Control) to -65.384 g·s (PSgel@Glycerol 100-90), which is attributed to the esterification reaction between glycerol macromolecules and starch molecules under high temperature conditions to form ester bonds, forming a sticky starch glue on the surface of the gel. Glycerol, as a plasticizer, makes the molecular chains of starch gel softer and more plastic, the molecular structure looser, and the surface more easily interacts with water, thus producing a sense of adhesion. The elasticity increased from 0.8890 and 0.9537 to 0.9617, which may be attributed to the strong hydrogen bond interaction between glycerol and starch molecules and the fact that wet heat treatment promotes the cross-linking and reorganization of molecular chains, improves the stability of the gel network, and thus enhances the elasticity of the gel. The chewiness increased from 1401.3163g / sec and 1281.4927g / sec to 1802.4277g / sec, which may be related to the high toughness of the gel. The texture results also further prove that solvent replacement and wet heat toughening treatment are effective methods to improve the mechanical properties of starch gels.
[0165] Determination of crystallinity of high toughness starch gel
[0166] The relative crystallinity (RC) of all samples was measured by X-ray diffraction (XRD, AxSD8Advance, Bruker, Karlsruhe, Germany). The water content of each powder sample was increased to 25% at room temperature, and then the sample was stored at 4 ° C for 24 hours to fully balance the water. The test parameters were set as follows: speed 1 ° / min, step size 0.01 ° / min, scanning range 5-40 °, 40 mA, 40 kV, Cu-kα radiation (K = 1.54). The RC value is the ratio of the crystalline peak area (Ac) between 5 ° and 28 ° (2θ) to the total peak area (A).
[0167] To further understand the synergistic effect of solvent replacement and wet-heat toughening treatment on the crystallization properties of the gels, X-ray diffraction studies were performed. Fig.14 PSgel@Control of Comparative Example 7 and PSgel@Control of Comparative Example 6 100-90 and PSgel@Glycerol of Example 24 100-90 X-ray diffraction pattern of the sample. Fig.14 As shown in the figure, all samples showed typical B-type crystals with characteristic peaks at 17°, 20° and 23°. There were obvious differences in the crystallization peak intensities of different samples, among which PSgel@Glycerol 100-90 The crystallization peak intensity of PSgel@Control 100-90The crystallization peak intensity of PSgel@Control sample is weak, while there is almost no crystallization peak, and the crystallinity is 8.92%, 3.35% and 0.95% respectively. This shows that solvent replacement assisted hydrothermal toughening treatment can promote the formation of crystals and increase the crystallization domain. This is because high temperature promotes the dissociation and rearrangement of the double helix structure of starch, and the weak cross-linking sites dissociate and rearrange to form strong cross-linking sites. In addition, the strong hydrogen bonds formed between glycerol molecules and starch molecular chains further increase the degree of recrystallization of starch.
[0168] Determination of High-Toughness Starch Hydrogel by Fourier Transform Infrared Spectroscopy
[0169] The infrared spectra of all samples were obtained by Fourier transform infrared (FTIR) spectrometer from Thermo Scientific, USA, with a scanning range of 400–4000 cm -1 , scanned 64 times, with a resolution of 4cm -1 Each spectrum used air as the background. Spectra were smoothed and baseline corrected using OMNIC 8.0 software and analyzed in the 950–1150 cm -1 Fourier deconvolution is performed within the range. By analyzing R 1047 / 1022 The absorbance at 37° was used to explore the changes in the short-range ordered structure of starch in the sample.
[0170] Fig.13 PSgel@Control of Comparative Example 7 and PSgel@Control of Comparative Example 6 100-90 and PSgel@Glycerol of Example 24 100-90 Fourier transform infrared spectrum of the sample (A.) and short-range density diagram (B.). Fig.13 As shown in Figure A, the overall shape of the infrared spectra of all samples is similar, indicating that no new compounds are formed after solvent replacement and wet heat toughening treatment. -1 A distinct broad band was observed in the range, which was related to the OH stretching vibration and the intermolecular hydrogen bonding of the pyranose ring. 100-90 ) compared to PSgel@Glycerol 100-90 The broad band of the sample is from 3358.67cm -1 and 3298.16cm -1 Reduced to 3278.63cm -1 , showing that the broad band shifts to the low-frequency band, which indicates that the hydrogen bonding interaction inside the starch gel is significantly enhanced. Fig.13 Figure B shows the R values of all samples obtained after Fourier deconvolution of the FTIR spectra. 1047 / 1022 Value. 1047cm-1 The absorbance at 1022 cm is related to the ordered double helix (crystalline region). -1 The absorbance at R indicates the changes in the amorphous region and disordered double helix of starch. 1047 / 1022 The value can represent the short-range ordered structure of starch and is mainly used to reflect the configuration of starch molecular chains. It reflects the local organization of the crystal array formed by the helix, which depends on the arrangement of the double helix. 100-90 ) compared to PSgel@Glycerol 100-90 The short-range order of the samples increased from 0.3773 and 0.3883 to 0.4141, which indicates that the wet heat toughening treatment can promote the rearrangement of the double helix in starch, change the conformation of the macromolecular chain, enhance the hydrogen bond interaction in starch gel and the reorganization of the crystalline domain.
[0171] Scanning electron microscopy determination of high toughness starch hydrogel
[0172] The cross sections of the samples were analyzed using a scanning electron microscope (SEM, S-4800, Hitachi Instruments Ltd, Tokyo, Japan). All samples were fully frozen in liquid nitrogen at -198°C for 2 min, immediately transferred to -80°C, and freeze-dried for 72 h. The network structure of the freeze-dried samples was observed using a scanning electron microscope under the conditions of 5 kV and 10 μA.
[0173] Fig.12 PSgel@Control of Comparative Example 7 (upper left picture), PSgel@Control of Comparative Example 6 100-90 (Top right) and PSgel@Glycerol of Example 24 100-90 (Lower row) Cross-sectional SEM images. As shown in the figure, all samples have a porous structure and appear honeycomb-like, but the pore size and pore density are different. 100-90 ) compared to PSgel@Glycerol 100-90 The gel network structure of the sample is denser, the pore size is smaller, and the pore wall thickness is thicker. The specific data are listed in Table 3.
[0174] Table 3PSgel@Control, PSgel@Control 100-90 and PSgel@Glycerol 100-90 Porosity characteristics
[0175]
[0176] Data are presented as mean ± SD (n = 3). Mean values marked with different letters (ac) in the same column are statistically significant (p < 0.05).
[0177] As shown in Table 3, compared with the control group, the pore size of the starch gel decreased from 0.0715 μm and 0.0523 μm to 0.0227 μm, the pore wall thickness increased from 0.1534 μm and 0.2224 μm to 0.4349 μm, and the pore number increased from 1564.33 / μm 2 and 1218 / μm 2 Reduced to 1017.67 / μm 2 The porosity decreased from 25.26% and 16.79% to 6.47%, indicating that the wet heat toughening treatment can significantly improve the pore characteristics of starch gel. This phenomenon is attributed to the fact that the wet heat toughening process promotes the migration of starch molecular chains, the high entanglement and reorganization between molecular chains, and the hydrogen bond interaction between glycerol molecules and starch molecular chains, which enhances the reorganization of the crystal domains.
[0178] Universality assay
[0179] Different types of starch, corn starch, wheat starch, sweet potato starch, cassava starch, indica rice flour, mung bean starch and pea starch were selected and universality was determined according to the method of the present invention. Figures 8 to 11 It can be seen that compared with the control group (PSgel@Control, PSgel@Control 100-90 ), the tensile stress and tensile strain of the samples were significantly higher than those of the control group, which shows that this method is universal.
[0180] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A modified starch hydrogel, comprising natural starch, water and a polyhydroxy compound; the water, the polyhydroxy compound and the natural starch are cross-linked to form a honeycomb network structure.
2. The modified starch hydrogel according to claim 1, characterized in that The polyhydroxy compound comprises one or more of glycerol, glucose alcohol, sucrose, erythritol, xylitol, maltitol, D-mannitol and sorbitol; the mass of the polyhydroxy compound is 2-8% of the mass of the modified starch hydrogel; the mass of the water is 52-58% of the mass of the modified starch hydrogel.
3. The modified starch hydrogel according to claim 1 or 2, characterized in that: The natural starch includes one or more of potato starch, corn starch, wheat starch, sweet potato starch, cassava starch, indica rice flour, mung bean starch and pea starch; the natural starch includes amylose and amylopectin; the mass of the amylose is 20-25% of the mass of the starch; the mass of the natural starch is 40% of the mass of the modified starch hydrogel.
4. The method for preparing the modified starch hydrogel according to any one of claims 1 to 3, comprising the following steps: The starch hydrogel and the polyhydroxy compound aqueous solution are mixed and subjected to a wet heat toughening treatment, in which part of the water in the starch hydrogel is replaced by the polyhydroxy compound to obtain a modified starch hydrogel; the temperature of the wet heat toughening treatment is 25 to 135°C.
5. The preparation method according to claim 4, characterized in that: The time of the wet heat toughening treatment is 15 to 120 minutes.
6. The preparation method according to claim 4 or 5, characterized in that: The mass ratio of the starch hydrogel to the polyhydroxy compound aqueous solution is (1-1.25):15; the mass concentration of the polyhydroxy compound in the polyhydroxy compound aqueous solution is 25-100%.
7. The preparation method according to claim 6, characterized in that: The mass concentration of water molecules in the starch hydrogel is 60%.
8. The preparation method according to claim 4, characterized in that: After the wet heat toughening treatment is completed, the product is immersed in water; the immersion temperature is 0 to 5°C, the number of times is 1 to 5 times, and the single immersion time is 5 to 30 minutes.
9. The preparation method according to claim 4, characterized in that: The preparation of the starch hydrogel comprises: gelatinizing starch slurry to obtain the starch hydrogel; the gelatinization power is 500-800W and the time is 3-4min.
10. Use of the modified starch hydrogel according to any one of claims 1 to 3 or the modified starch hydrogel prepared by the preparation method according to any one of claims 4 to 9 in food.
Citation Information
Patent Citations
Medical hydrogel dressings and preparation method thereof
CN101982202A
Method for modifying starch by using molasses
CN108997507A
Method for improving anti-static, anti-abrasion and water lubricating performance of starch capsules
CN109942901A
Starch-based hydrogel, preparation method thereof and hemostatic dressing
CN114213716A
Modified hydroxypropyl starch, preparation method and application thereof, starch hydrogel and application thereof
CN114573722A
Cited By
Modified starch for stopping bleeding and promoting repair as well as preparation method and application of modified starch
CN120988149A